Rangelands biodiversity in presaharian Tunisia - Ferchichi A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Rangeland in presaharian Tunisia shelter a rich flora which include about 836 species. 100 of them are specific to presaharian Tunisia and 21 species are endemic. Since some decades, because of the rapid tendency to the total sedentariness of the population, the breaking of the great collective lands and the disappearance of transhumances, presaharian Tunisia rangelands are increasingly submitted to an irrational and anarchic exploitation that induce a qualitative and a quantitative degradation. 43 species are considered as threatened of extinction and many habitats (oueds, steppes etc.) are exposed to destruction.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)